Simulation and techno-economic analysis of energy cane pyrolysis for bio-oil production using Aspen Plus - Thomas Rafael de Oliveira; Antonio Carlos Luz Lisboa (Heliyon)
This work investigates the energy cane pyrolysis by process simulation in Aspen Plus, evaluating which variety maximizes bio-oil yield with further economics to evaluate process feasibility. Three cultivars were selected: two natural, Saccharum robustum and Saccharum spontaneum, and one, IACSP955000, generated by a breeding program. Firstly, 100 kg/h of wet biomass entered a stoichiometric reactor (RSTOIC) at 450 °C and 40 bar, generating biochar, bio-oil and gases. Secondly, a sensitivity analysis using CSTR determined its volume for an equivalent bio-oil yield. The economics involved two scenarios: 1) Two years payback and 10 years plant life; 2) 2.71 years payback and 20 years plant life. The Saccharum spontaneum produced the highest bio-oil yield. A 50 L CSTR produced bio-oil yield compared to the RSTOIC. The techno-economic results were: for the first scenario, bio-oil price of US$ 1.49/L and an internal rate of return (IRR) of 34 %; for the second, bio-oil price of US$ 1.15/L and an IRR of 16 %. The bio-oil price was 2.1 times higher than the international, suggesting either the employment of catalytic pyrolysis or energy integration to increase the bio-oil yield or to improve its quality.